(3eMGSHI GdJcGdja GdaYdjI (B/s - (3GdQRb, UGdM YHO Gddgs; (3hQGO Ndjd, YWG Gddg s ((3YeGf(B: s (3OGQ GdRgQGf ddfTQ hGdJhRjY(B, s, 2012)
(3bjGS GdJcGdja GdaYdjI, WHjI eMGSHI GdJcGdja, GdJbGQjQ GdeGdjI aj GdefTBJ GdUfGYjI, fXQjGJ GdJcGdja GdaYdjI, bjGS JcdaI GdehGO GdeHGTQI h JcdaI GdYed GdHTQj h bjGS GdJcGdja GdUfGYjI ZjQ GdeHGTQI , GdeMGSHI Yf GdJcGdja GdaYdjI , fXe bjGS GdJcGdja GdaYdjI, fXGe JcGdja GdChGeQ GdGfJGLjI h GdeQGMd GdGfJGLjI , fXGe JcdaI GdebGhdGJ , JcGdja GdefJLGJ GdeTJQcI h GdaQYjIs
(3GdedGMb U(B.439s
Keywords: (3GdeMGSHIs; (3eMGSHI GdJcGdjas